Formulasi Model Sistem Pemidanaan Anak Di Indonesia - I Dewa Putu Gede Anom Danujaya (Jurnal Daulat Hukum, 2018)
AbstractThis article aims to describe the perceptions and factors that cause crime in the environment of children as well as the formulation / model of the child criminalization system in Indonesia. The criminal system policy in an effort to protect children in the future should be able to improve the products of laws / regulations currently in Law No.11 / 2012. The product of a law / system must be more flexible according to the fast progress of the times. Especially with the emergence of issues especially related to the age limit of criminal responsibility, criminal guidelines, and types of sanctions. The refinement basically still refers to the concept of the 2012 Criminal Code (although it is still in the drafting and ratification stage) which is expected to be clearer, more comprehensive, detailed in the formulation of the article, and with the spirit of paying attention to the considerations of various international documents besides that, the Criminal Code of foreign countries can also as material for comparative studies and completeness in an effort to formulate new regulations or systems that will be implemented later.Key words: child criminal system, child protectionAbstrakArtikel ini bertujuan untuk menguraikan tentang persepsi dan faktor penyebab kejahatan dalam lingkungan anak serta formulasi/model sistem pemidanaan anak di Indonesia. Kebijakan sistem pemidanaan dalam upaya perlindungan terhadap anak dimasa yang akan mendatang hendaknnya bisa lagi menyempurnaan produk undang-undang/peraturan yang dalam dalam UU No.11/2012 sekarang ini. Produk suatu Undang-undang/sistem harus lebih fleksibel sesuai dengan cepatnya kemajuan perkembangan zaman. Apalagi dengan munculnya isu-isu khususnya terkait dengan batas usia pertanggungjawaban pidana, pedoman pemidanaan, dan jenis-jenis sanksi. Penyempurnaan itu pada hakikatnya tetap mengacu pada konsep KUHP 2012 (walaupun masih dalam tahap rancangan dan pengesahan) yang diharapkan lebih jelas, komprehensip, rinci dalam rumusan pasalnya, serta dengan semangat tetap memperhatikan pertimbangan berbagai dokumen internasional selain itu, KUHP negara-negara asing juga bisa sebagai bahan studi perbandingan dan kelengkapan dalam upaya penyusunan peraturan atau sistem baru yang akan diterapkan nantinya.Kata kunci: sistem pemidanaan anak, perlindungan anak.